PERPADUAN NILAI DAKWAH DAN ESTETIKA DALAM NOVEL KAMBING DAN HUJAN KARYA MAHFUD IKHWAN - Mazka Hauzan Naufal (Islamic Communication Journal, 2018)
The growth of islamic literature keeps a problem. For some critics, many works of fiction labeled "islamic literature" are problematic in terms of writing techniques and the value of aesthetic. Amidst the stream of criticism that highlighted the weaknesses of islamic literary products, emerged several literary works, which although not specifically labeled "islamic literature", contained symbols and islamic moral teachings that won prestigious literary awards. One of them is the novel Kambing dan Hujan by Mahfud Ikhwan. Using Robert Stanton's structural analysis approach, this article intends to describe how the values of da'wah and aesthetic values are combined in the novel Kambing and Hujan. Based on the analysis, two conclusions were drawn. First, the novel Kambing dan Hujan has structural density. Every intrinsic element is interrelated in harmony. Second, the novel Kambing and Hujan succeeded in combining aesthetic values (marked by structural density and harmony between elements) with the value of da'wah (which was marked by the existence of the content of Islamic teachings in it).Â